Sikap Pemustaka terhadap Layanan Perpustakaan di Perpustakaan Padang Panjang - Aldila, Vaze; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractBased on the results of the study, the following is concluded. The attitude of visitors towards library services in the Padang Panjang City Library. 1) the attitude of the librarian in the Padang Panjang City Library has been very positive, seen from the attitude of the librarian who is able to serve users wholeheartedly and help users when needed. 2) the visitor's attitude is very positive towards the collection services available at the Padang Panjang City Library. This can be seen from a collection of collections quickly so it is very easy to find the desired collection. 3) visitors' attitudes towards the facilities are also very positive as seen from the facilities at the Padang Panjang City Library, neat reading tables and reading chairs that allow visitors and make visitors comfortable visiting the Padang Panjang City Library.Keyword:Â Library, Collection, AttitudeÂ